Delayed reception of live blowfly (Calliphora vicina and Chrysomya rufifacies) larval samples: implications for minimum postmortem interval estimates - Melanie S. Archer; Stephanie D. Jones; James F. Wallman (Oxford University Press, 2018)
Forensic entomology evidence collected by police and mortuary staff may be delayed in getting to the entomologist. Live samples may continue developing and alter minimum postmortem interval (PMImin) estimates. This study investigated development of simulated evidential samples of Calliphora vicina Robineau-Desvoidy and Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) maggots. Maggots of each species were studied in three developmental classes: "small" (late second/early third instar), "mid" (mid third instar) and "large" (late third instar). Seven replicates of 11 maggots in each class were assigned without food to four treatments: (1) 24 h at 20 °C; (2) 24 h at 4 °C; (3) 48 h at 20 °C and (4) 48 h at 4 °C. There was a significant difference in absolute length change across treatments, reflecting size for C. vicina, and interaction between size, time and temperature for Ch. rufifacies. Calliphora vicina maggots showed minimal mortality, and most second instar larvae moulted by the experiment's end. Chrysomya rufifacies showed heavy mortality and minimal moulting from the second to third instar. Only "large" Ch. rufifacies maggots kept at room temperature for 48 h pupariated. Since these results confirm that development can continue in live unfed maggot samples after their collection, it is not advisable to delay their preservation.